DAMPAK PENAMBANGAN EMAS TERHADAP LINGKUNGAN DI DESA TAMILOUW KECAMATAN AMAHAI, KABUPATEN MALUKU TENGAH - Debbi V Pattimahu; Antho Netty Siahaya; Terezia V Pattimahu (JURNAL HUTAN PULAU-PULAU KECIL, 2021)
Natural resource management that does not pay attention to the principles of conservation of natural resources and the environment will have negative implications for environmental sustainability. With the discovery of gold on the coast of Tamiouw Village at this time, residents' activities have shifted to gold mining activities in the coastal area of Tamilouw. This study aims to determine the impact of gold mining on the physical environment in Tamilouw Village, Amahai District, Central Maluku Regency, as well as to determine the impact of gold mining on the social and economic environment of the local community. The research was conducted using non-experimental methods, namely exploratory descriptive, field observations and literature study. The results showed that gold mining carried out in Tamilouw Village uses mercury in the process of separating gold from sand, although there are also some people who carryout traditional processing. What some people are worried about is that the disposal of mercury waste is not carried out according to the required procedures, so that it will have an impact on environmental damage. The existence of mining activities does not affect the social aspects, namely education, health and age and gender; while from the economic aspect, it also contributes to increasing people's income. Keywords : Gold mining, environment, Tamilouw Villageout traditional processing. What some people are worried about is that the disposal of mercury waste is not carried out according to the required procedures, so that it will have an impact on environmental damage. The existence of mining activities does not affect the social aspects, namely education, health and age and gender; while from the economic aspect, it also contributes to increasing people's income.